Gemcitabine/Cisplatin Treatment Induces Concomitant SERTAD1, CDKN2B and GADD45A Modulation and Cellular Changes in Bladder Cancer Cells Regardless of the Site of TP53 Mutation - da Silva, Glenda Nicioli; Filoni, Leandro Toshio; Salvadori, Maria Cecília; Salvadori, Daisy Maria Fávero [UNESP] (Springer Nature, 2018)
Simultaneous use of cisplatin (CIS) and gemcitabine (GEN) for treating bladder cancer has increased because of their complementary effects. However, the molecular mechanisms underlying the activities of these two antineoplastic drugs are not fully known. Here, molecular biology techniques and microscopy were used to investigate transcriptomic and morphological changes in low and high-grade urinary bladder transitional carcinoma cell lines [RT4 - wild type TP53; 5637 - two TP53 mutations, one in codon 72 (Arg-Pro) and other in codon 280 (Arg-Thr) and T24 - in-frame deletion of tyrosine 126 in the TP53 allele] simultaneously treated with CIS/GEN. Gene expression profile was evaluated by PCR arrays; cell morphology by scanning and transmission electron microscopy, and apoptosis was analyzed using fluorescent dye. Results showed concomitantly upregulation of CDKN2B (G1/S transition), GADD45A (DNA repair and apoptosis) and SERTAD1 (regulation of transcription) gene, increased number of nuclear chamfers and apoptotic cells, and reduced number of microfilaments, organelles and in the size of the nucleus in 5637 and T24 cells after simultaneous treatment with CIS/GEN. In conclusion, independently of the TP53 mutation status and tumor grade, CIS/GEN induced gene modulation accompanied by changes in cell morphologies, which confirm the antiproliferative activity of the treatment protocol. These findings help to understand the pathways modulated by these antineoplastic agents and may provide insights for anti-cancer chemotherapy.
Keywords: Bladder cancer; Cell morphology; Chemotherapy; Cisplatin; Gemcitabine; Gene expression